2021
DOI: 10.1111/sifp.12144
|View full text |Cite
|
Sign up to set email alerts
|

Free Access to a Broad Contraceptive Method Mix and Women's Contraceptive Choice: Evidence from Sub‐Saharan Africa

Abstract: Financial barriers may restrict women's ability to use their preferred contraceptive methods, especially long-acting reversible contraceptives (LARC). Providing free access to a broad contraceptive method mix, including both LARC and short-acting reversible contraceptives (SARC), may increase contraceptive use, meet women's various fertility needs, and increase their agency in contraceptive decisions. Linking facility and individual data from eight countries in sub-Saharan Africa, we use a propensity score app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…The findings of this study highlight the importance of gender equality in decision making by affirming the evidence finding that enhancing women's autonomy improves the uptake of contraception use [24,25]. Strategies to improve women's autonomy include improving women's socioeconomic status, enhancing their education and dismantling of cultural laws that support gender inequality [14,26]. Increasing the socio-economic status of women is one of the most powerful tools that impacts significantly on reproductive choice [26].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The findings of this study highlight the importance of gender equality in decision making by affirming the evidence finding that enhancing women's autonomy improves the uptake of contraception use [24,25]. Strategies to improve women's autonomy include improving women's socioeconomic status, enhancing their education and dismantling of cultural laws that support gender inequality [14,26]. Increasing the socio-economic status of women is one of the most powerful tools that impacts significantly on reproductive choice [26].…”
Section: Discussionsupporting
confidence: 57%
“…Other cultural factors, such as those that promote men as heads of relationships, may influence decision-making in women who are educated [ 23 25 ]. All these issues are essential indicators of gender equality and are women’s rights issues [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a study in Colombia showed that a reduction in the price of levonorgestrel-releasing implants was immediately accompanied by an increase in demand, studies in Indonesia and Bangladesh showed that sales of different types of contraceptives were inelastic to price reductions [21][22][23]. Recent evidence gathered from eight sub-Saharan countries has suggested that rendering family planning services completely free of charge might be a promising strategy to increase access to contraception [24]; however, several systematic reviews have found no rigorous evaluations of the effects of user fee removal initiatives on contraception use [20,25].…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic gradients in the likelihood of long-acting reversible contraceptive (LARC) use in sub-Saharan Africa indicate that cost barriers may be prohibitive for the poorest women, particularly for LARC methods that may include fees for provider insertion and removal in addition to the commodity itself. 5 , 6 There is substantial regional variability in the proportion of women with unmet need for contraception who cite lack of access or high cost as a reason for nonuse: an analysis of the Demographic and Health Surveys (DHS) Program found that only 4% to 8% of women cited lack of access as a reason for nonuse overall, although this proportion was as high as 15% in Middle Africa and 10% in West Africa. 7 …”
Section: Introductionmentioning
confidence: 99%